RESPONSIBILITAS PEMERINTAH KOTA LHOKSEUMAWE DALAM PENGELOLAAN PABRIK ES DAN GUDANG IKAN DI PANGKALAN PENDARATAN IKAN (PPI) PUSONG KOTA LHOKSEUMAWE - Lisa Iryani (Program Studi Administrasi Bisnis, 2021)
The Pusong Fish Landing Base (PPI) of Lhokseumawe City is one of the main infrastructures in supporting capture fisheries business, namely the construction of an Ice Factory and fish warehouse in 2009 and completed in 2011 with Special Autonomy and DAK funds of around Rp. 2 billion more. The management of the Pusong Ice Factory was chaotic, so that later the impact of the arrears in the electricity bill was a power cut by PLN, so the factory stopped operatingThis study aims to analyze and describe the responsibility of the Lhokseumawe City government in managing the Pusong fish landing base and the causes of the non-optimal management carried out by the Lhokseumawe City government. The methodology used in this study is a qualitative method through observation, interviews and documentation. In this study, it was found that the alleged weak analysis of the planning for the construction of the Lhokseumawe Pusong ice factory resulted in the provision of facilities and infrastructure at the ice factory being inadequate to produce ice blocks in large quantities and not in accordance with the standards for an ice factory. The lack of optimal elaboration of appropriate policies and the lack of qualified human resources in managing the ice factory at PPI Pusong Lhokseumawe.